2018
DOI: 10.1073/pnas.1712324115
|View full text |Cite
|
Sign up to set email alerts
|

Desynchrony between brain and peripheral clocks caused by CK1δ/ε disruption in GABA neurons does not lead to adverse metabolic outcomes

Abstract: Circadian disruption as a result of shift work is associated with adverse metabolic consequences. Internal desynchrony between the phase of the suprachiasmatic nuclei (SCN) and peripheral clocks is widely believed to be a major factor contributing to these adverse consequences, but this hypothesis has never been tested directly. A GABAergic Cre driver combined with conditional casein kinase mutations ( ) was used to lengthen the endogenous circadian period in GABAergic neurons, including the SCN, but not in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 79 publications
(120 reference statements)
6
27
0
Order By: Relevance
“…According to this last hypothesis, food mistiming can uncouple peripheral clocks in metabolic tissues from the central clock, causing internal misalignment [41]. However, to date, there is no direct evidence that internal desynchrony per se adversely affects glucose control [42], suggesting that the first two mechanisms may be most important.…”
Section: Impact Of Circadian Disruption On Glucose Control In Healthymentioning
confidence: 99%
“…According to this last hypothesis, food mistiming can uncouple peripheral clocks in metabolic tissues from the central clock, causing internal misalignment [41]. However, to date, there is no direct evidence that internal desynchrony per se adversely affects glucose control [42], suggesting that the first two mechanisms may be most important.…”
Section: Impact Of Circadian Disruption On Glucose Control In Healthymentioning
confidence: 99%
“…22,23 For example, CK1δ/ε is a priming kinase for PER2 phosphorylation and a Discordant mouse model caused by CK1δ/ε disruption in GABAergic neurons shows a long (27.4 hour) behavioral period. 24 Hence, the current view is that circadian rhythms are governed by a very complex system that works in a well-organized way to coordinate endogenous circadian rhythms in gene expression and physiological metabolism. The analysis of the circadian transcriptome in 12 mouse organs demonstrated that more than 40% of all protein coding genes and 1,000 noncoding RNAs oscillate in an organ-specific manner and many of these rhythmic transcripts peaked during transcriptional "rush hours" preceding dawn and dusk.…”
Section: Circadian Clocksmentioning
confidence: 99%
“…At the molecular level, mammalian circadian clocks consist of transcription-translation feedback loops in which positive limb proteins (BMAL1, CLOCK and NPAS2) drive the expression of negative limb proteins (PERIOD1-3 and CRYPTOCHROME1-2), which subsequently inhibit the activity of the positive limb (Takahashi, 2017). This molecular feedback loop has a period of ∼24 h. The period length is set by the degradation rate of negative limb proteins, with casein kinase 1 delta and epsilon (CK1δ/ε) being important for setting the speed of the clock by controlling the stability of PERIOD proteins (Etchegaray et al, 2009;Meng et al, 2008;van der Vinne et al, 2018). The molecular components of the circadian clockwork are widely expressed, and cell-autonomous circadian clocks are present in nearly all cells of the body.…”
Section: Introductionmentioning
confidence: 99%